Rehabilitation of foal with extensor tendon laceration: Case report - de Sousa, Francielle; Oliveira Alves, Arthur Lúcio; Marins Costa, Otávio; Lima Ribeiro, Gustavo; de Almeida Silva, Laura (Pubvet, 2022)
Wounds and lacerations are quite common in horses. Of these, the rupture of tendons, especially the digital extensor tendon, is one of the forms that causes much concern because it compromises the animal’s locomotion in addition to being able, in most cases, to cause permanent or intermittent hyperflexion of the involved limb. Thus, they must be well treated and medicated according to each stage of the healing process. Therefore, the objective of this work is to report the case of a filly that had a laceration of the common digital extensor tendon, showing the management and methods that were used for its treatment and rehabilitation. In addition, it seeks to describe the procedures used to treat total rupture of the common digital extensor tendon due to cord burn; paying attention to the anatomy of the pelvic limb. To support the theme addressed in this study, a literature review was sought on the anatomy of the tendons in horses, the rupture of the digital extensor tendon, as well as the diagnosis and treatment of the animal compromised by the rupture. The research has a qualitative character when describing the procedures used from contact with the animal to its rehabilitation structured by the case study. The material consulted was based on books, scientific articles, consulted mostly on the internet on reliable sites such as university journals and technical manuals. Through the case report, it was possible to observe from the initial care of the foal, with a view to diagnosis and treatment until its rehabilitation. It was noticed that the physical examination, in this case, is the best way to diagnose the laceration of the digital extensor tendon and the forms of treatment vary, with the use of plaster and controlled walks being positive alternatives for rehabilitation. At the end of the study, it was possible to conclude that the procedures adopted were satisfactory for wound healing and rehabilitation of the foal.